A process for developing multisectoral strategies for zoonoses: the case of leptospirosis in Fiji - Simon A. Reid; Anna Rodney; Mike Kama; Peter S. Hill (BMC, 2017)
Abstract Background Zoonotic diseases such as leptospirosis occur as a result of the often complex interactions that exist at the human-animal-environment interface. The most obvious consequence of this complexity is the need for the health sector to partner with institutions in other sectors of society such as agriculture, labour and local government. This multisectoral engagement is complicated by the different agendas and cultures of the various institutions and their ability to "see" their role and ant benefits in a collaborative response. Methods The research used a realist review methodology combined with systems thinking frameworks to determine the optimal strategy and governance for the prevention and control of leptospirosis in Fiji. The process included facilitated workshops with multiple stakeholders to determine the needs, issues and potential interventions that was guided by a synthesis of locally available data and information on the impact of leptospirosis. This process was informed by interviews with bureaucrats from different government ministries. Results Stakeholders concurred that leptospirosis generally only received wide-spread attention in outbreaks, when there is media coverage of deaths or a large number of hospitalisations. In general, all ministries expressed support for a multisectoral strategy but saw the Ministry of Health and Medical Services as the lead agency with overall responsibility. The final consultation workshop yielded a clearly articulated goal to reduce the case fatality rate attributable to leptospirosis by 50% by 2020 and 4 overarching strategies: 1) improved clinical management of leptospirosis, 2) improved surveillance for leptospirosis, 3) enhanced communication to minimise risk and improve health seeking behaviours, and 4) strengthening coordination and governance structures. Conclusion Human mortality and morbidity remained the primary drive for government action, defining leptospirosis as a human health problem. The process of deliberative consultation, and the engagement of multidisciplinary partners has provided a platform for collaborative policy development, and a consensus for a National Action Plan from which further negotiated collaboration will be possible.